Method for preparing high-performance anti-reflection structure on surface of infrared window based on femtosecond laser multi-path focus multiplexing

The femtosecond laser multi-channel focus multiplexing technology is used to prepare a sub-wavelength enhancing structure with high depth diameter ratio on the infrared window surface, which solves the problem of dimensional regulation of sub-wavelength micro-nano processing in the prior art and the thermal expansion of traditional urge films, and achieves the effects of high transmittance and mechanical stability.

CN119747845AActive Publication Date: 2025-04-04JILIN UNIVERSITY

Patent Information

Application Number
CN202510107361.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-23
Publication Date
2025-04-04
Estimated Expiration
2045-01-23

AI Technical Summary

Technical Problem

The prior art is difficult to finely adjust the subwavelength micro-nano processing size to improve the anti-reflection effect, and traditional amplicon films have problems of thermal expansion and lattice mismatch.

Method used

Using femtosecond laser multi-channel focus multiplexing technology, multiple marking processing is performed on the infrared window surface by scanning galvanometer and high-precision three-dimensional displacement platform to form a sub-wavelength enhancing structure with high depth diameter ratio.

Benefits of technology

A subwavelength enhancing microstructure with a period of less than 4 μm and a depth diameter ratio of up to 18 is achieved, which improves transmittance and mechanical stability and reduces surface Fresnel reflection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119747845A_ABST
    Figure CN119747845A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a high-performance anti-reflection structure on the surface of an infrared window based on femtosecond laser multi-path focus multiplexing, and belongs to the technical field of laser processing. Leveling the sample table; a high-aspect-ratio and high-transmittance sub-wavelength structure is prepared by combining multi-path focus multiplexing with wet etching; according to the method, a scanning galvanometer is combined with a high-precision three-dimensional displacement platform, and femtosecond laser is used for carrying out multiple times of lineation processing at the same horizontal position, that is, during first lineation processing, a laser focus is focused on the upper surface of a sample, and a preliminary small-period sub-wavelength anti-reflection structure is formed; then, the laser focus is negatively defocused, meanwhile, the polarization direction of the laser beam is changed, the laser power and the scanning speed are increased, and secondary scribing machining is conducted, so that the problems of rough surface appearance, low depth-to-width ratio of the structure, poor overall appearance consistency and the like in existing research are solved, and it is proved that when an anti-reflection structure with the higher anti-reflection effect is prepared, the anti-reflection effect is good. A skillful processing means is not available, and a laser direct processing method must be adopted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of laser processing, and in particular relates to a method for preparing a high-performance anti-reflection structure on an infrared window surface based on femtosecond laser multi-path focus multiplexing. Background Art

[0002] As an important part of the infrared detection system, the infrared window should not only separate the environment and the imaging system and protect the detector, but also improve the transmittance of infrared radiation. Therefore, the selection of infrared window materials is very important. Zinc sulfide has the advantages of good thermal stability, high hardness and high transmittance. It is a common infrared window material and is widely used in fairings, infrared lenses, infrared windows and other fields. However, the refractive index of air and infrared windows is different, which will produce surface Fresnel reflection, resulting in surface reflection loss and affecting the quality of infrared imaging. The traditional method to reduce reflection loss is to coat a single or multi-layer anti-reflection film on the surface of the infrared window. However, this method has the disadvantages of easy shedding of the film layer due to thermal expansion and lattice mismatch between the film layer and the substrate material, and limited anti-reflection effect on wide-spectrum infrared signals. Compared with coating the anti-reflection film on the surface of the infrared window, using short-pulse laser to directly prepare a sub-wavelength high-performance anti-reflection structure on the sample surface can narrow the refractive index gap between the air and the interface and effectively reduce the surface Fresnel reflection. No matter what parameters are used for single processing, it cannot meet the target requirements. Therefore, it is necessary to use a multi-channel focus multiplexing processing method to obtain better results. Summary of the invention

[0003] In view of the problems in the prior art such as the difficulty in finely controlling the sub-wavelength micro-nano processing size to improve anti-reflection, the present invention provides a method for preparing a high-performance anti-reflection structure on the surface of an infrared window based on femtosecond laser multi-focus multiplexing. The method uses a scanning galvanometer in combination with a high-precision three-dimensional displacement platform to perform multiple scribing processes at the same horizontal position using a femtosecond laser, that is, during the first scribing process, the laser focus is focused on the upper surface of the sample to form a preliminary small-period sub-wavelength anti-reflection structure; then, the laser focus is negatively defocused (located below the surface), and the polarization direction of the laser beam is changed at the same time, and the laser power and scanning speed are increased to perform the second scribing process, which solves the problems of rough surface morphology, low structural aspect ratio, and poor overall morphology consistency in existing studies, and proves that when preparing an anti-reflection structure with a higher anti-reflection effect, tricky processing methods are not desirable, and a laser direct processing method must be adopted.

[0004] The present invention is achieved through the following technical solutions:

[0005] The method for preparing a high-performance antireflection structure on the surface of an infrared window based on femtosecond laser multi-path focus multiplexing specifically comprises the following steps:

[0006] (1) Sample fixation and dust removal system construction;

[0007] The specific steps are as follows: clamp the sample at the edge with a special fixture and fix the fixture with screws and bolts; use an air compressor to provide the gas source, and the gas route consists of a pipeline, an adapted needle-type air blowing joint and a pressure regulating valve; use a fixing rod to fix the needle-type air blowing joint on the side of the translation stage so that it can directly act on the processing area, and then blow the gas to the processing area through the nozzle of the needle-type air blowing joint; control the processing parameters through the pressure regulating valve to keep the gas state unchanged before leveling the sample stage and during the processing;

[0008] (2) Leveling of the sample stage;

[0009] (3) Multi-channel focus multiplexing combined with wet etching to prepare high aspect ratio and high transmittance sub-wavelength structures;

[0010] The specific steps are as follows: during the first scanning process, the laser is first focused on the upper surface of the sample, the horizontal position remains unchanged, the laser power is set to W1, the scanning speed is set to V1, and a small-period subwavelength anti-reflection microstructure is prepared on the sample surface. Subsequently, the focus of the femtosecond laser is negatively defocused, the laser power is increased to W2, the scanning speed is increased to V2, and the polarization direction of the light beam is rotated 90° at the same time. The second processing is performed at the same horizontal position, and finally, combined with wet etching, a high-quality, high-aspect-ratio subwavelength structure is prepared on the surface of the infrared window.

[0011] Furthermore, in step (2), the leveling of the sample stage specifically includes the following steps:

[0012] First, the femtosecond laser emitted by the laser passes through the first attenuation plate VDN1, and then is incident on the first convex lens L1 and the second convex lens L2 for beam expansion, and then is incident on the first half-wave HWP1, and then is incident on the first Glan prism GL1 after passing through the reflector R1, and then is uniformly incident on the entrance pupil of the scanning galvanometer GS after passing through the second half-wave plate HWP2, and then is emitted from the scanning galvanometer GS and passes through the third convex lens L3 and the fourth convex lens L4 respectively, and then is reflected by the reflector R2 and focused by the objective lens OL in turn, and then is incident on the infrared window sample surface on the hollow sample stage; the illumination light source LED is fixed above the hollow sample stage, so that the white light emitted by the illumination light source LED passes through the fifth L5 and the sixth convex lens L6 and then enters the objective lens OL; the illumination light passes through the reflector R2 and is reflected by the transmitting mirror R3 to the seventh convex lens L7 and is focused and imaged into the CCD, and finally the three-dimensional displacement stage and the CCD are connected to the computer terminal to monitor the leveling process of the sample stage in real time and level the sample stage.

[0013] The first half-wave plate and the first Glan prism constitute a light attenuation system, and it is necessary to ensure that the light intensity is precisely controlled within a precise range during processing to obtain an ideal structural size.

[0014] Furthermore, the sample stage is leveled, and the specific steps are as follows:

[0015] With the two perpendicular sides of the sample as the X-axis and Y-axis, the three-axis stepper motor is adjusted by computer to move between the two points (0, 0) and (1.5cm, 0), and the X-direction leveling knob is adjusted at the same time until the laser can scan a uniform damage line with a length of 1.5cm and a width of 5μm. At this time, the X-direction leveling is completed; similarly, the laser is used to draw a line between the two points (0, 0) and (0, 1.5cm) and the Y-direction leveling knob is used to level the Y direction; at this time, the laser can directly write a uniform width damage line in both the X and Y directions, indicating that the sample stage is perpendicular to the focused laser beam, the sample stage leveling is completed, and the position of the sample stage is fixed.

[0016] Furthermore, in step (3), the laser scanning method used is point-by-point scanning, and the spacing between each exposure point is in, is the focused spot diameter, λ is the laser wavelength, and NA is the numerical aperture of the objective lens OL.

[0017] Furthermore, in step (3), the laser power W1 used in the first processing is twice the infrared window surface damage threshold, the laser power W2 used in the second processing is 2-3 times the infrared window surface damage threshold, the scanning speed V1 used in the first processing is 10-20 μm / s, and the scanning speed V2 used in the second processing is 20-30 μm / s.

[0018] Furthermore, in step (3), the period of the small-period subwavelength anti-reflection microstructure prepared by the first processing is less than 4 μm.

[0019] Furthermore, in step (3), the polarization direction of the light beam is rotated 90°, specifically by controlling the second half-wave plate to change the polarization direction of the light beam into vertical polarization processing, and the scanning directions are two completely opposite directions perpendicular to the laser polarization.

[0020] Furthermore, in step (3), the wet etching is to heat the processed sample in a concentrated sulfuric acid solution water bath for a period of time, and then use a sodium hydroxide solution with a mass fraction of 5%-10% to corrode it.

[0021] The principle of the method for preparing a high-performance antireflection structure directly on the surface of an infrared window based on femtosecond laser multi-path focus multiplexing of the present invention is as follows:

[0022] The mechanism of sub-wavelength structure formation: through pulsed laser irradiation, the material structure is destroyed, thereby transforming the surface and interior of the material. For femtosecond short-pulse lasers, the material absorbs laser energy through photoionization and avalanche ionization, is excited in a very short time, and the electron density and temperature rise rapidly, eventually forming a high-density, high-temperature electron gas, and the material is destroyed by the plasma explosion.

[0023] Sub-wavelength diffraction theory: When the incident light is perpendicular to the anti-reflection sub-wavelength structure, the period of the anti-reflection structure is constrained by the following conditions:

[0024]

[0025] Among them, n ZnS and n air are the refractive indices of the substrate and air, respectively, and λ is the incident wavelength of the anti-reflection band. Therefore, the optimal period of the anti-reflection microstructure in the long-wave infrared band (8-12μm) is about 3μm. In addition, according to the effective medium theory, the anti-reflection microstructure layer can be equivalent to a thin film. According to the thin film interference theory, the thickness corresponding to the array anti-reflection height h should be:

[0026]

[0027] Among them, n eff and k are the effective refractive index and constant of the antireflection structure (k = 0, 1,

[0028] 2, 3...). In addition, the transmittance T of the antireflection microstructure is:

[0029]

[0030] In order to obtain the maximum T, the optimal n eff It should be 1.48. Therefore, for the long-wave infrared band, the structure height h is more suitable to be above 1.8μm.

[0031] Principle of multi-channel focus multiplexing control: Since no matter what parameters are used for single processing, the requirements for reducing Fresnel reflection loss cannot be met, multiple scans are required to obtain better results. First, a laser beam with a power higher than the threshold is used to scan the surface of the material for the first time to form a preliminary small-period subwavelength anti-reflection structure. Then, based on the first scan, the laser focus is negatively defocused, and the polarization direction of the laser beam is changed at the same time, and then the laser energy and scanning speed are increased to scan the surface of the material for a second or multiple times. This step is intended to further refine the micro-nano structure to the subwavelength level and optimize the shape and size of the structure. In summary, the shape, size and position accuracy of the subwavelength structure can be gradually corrected and optimized by using the multi-channel focus multiplexing method. By adjusting these parameters, the equivalent refractive index of the subwavelength structure can be accurately controlled to match the refractive index of the adjacent medium, thereby reducing reflections and strengthening the internal connections and support structures of the subwavelength structure to improve its mechanical stability and durability.

[0032] Compared with the prior art, the advantages of the present invention are as follows:

[0033] (1) Compared with the conventional femtosecond laser-induced surface subwavelength structure, the method of the present invention can realize a subwavelength anti-reflection microstructure with a period of less than 4 μm and a depth-to-diameter ratio of up to 18;

[0034] (2) By adjusting the polarization direction of the light beam during the processing, the flatness of the structure edge and the uniformity of the microstructure can be flexibly improved;

[0035] (3) By cooperating with the dust removal system, the measurement error and poor processing quality caused by the debris generated on the sample surface during the processing can be improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] In order to more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the following is a brief introduction to the drawings required for the specific embodiments or the description of the prior art. In all the drawings, similar elements or parts are generally identified by similar reference numerals. In the drawings, the elements or parts are not necessarily drawn according to the actual scale.

[0037] Figure 1 This is a schematic diagram of the optical path of a femtosecond laser three-dimensional galvanometer processing system combined with multi-path focus multiplexing to directly prepare an anti-reflection structure on the surface of an infrared window of the present invention:

[0038] In the figure, VND1-first attenuation plate, L1-first convex lens, L2-second convex lens, HWP1-first electrically controlled half-wave plate, R1-first reflector, GL1-first Glan prism, HWP2-second electrically controlled half-wave plate, GS-scanning galvanometer, L3-third convex lens, L4-fourth convex lens, R2-second reflector, OL-objective lens, three-dimensional translation stage (including Z-axis piezoelectric positioning platform, three-axis stepping motor, two-axis adjustment platform), LED-illumination light source, R3-third reflector, L5-fifth convex lens, L6-sixth convex lens, L7-seventh convex lens, CCD-high-definition camera;

[0039] Figure 2 A schematic diagram of a reflective objective lens processing device used in the present invention;

[0040] Among them, (a) is the structural state after the first processing when the focus is focused on the sample surface; (b) is the structural state after the second processing when the focus is moved to the inside of the sample at the same horizontal position with a negative defocus amount;

[0041] Figure 3 A schematic diagram for simulating the transmittance of sub-wavelength structures with different periods and depths, as well as simulating the light field during laser processing;

[0042] Figure 4The power is 234μW when preparing sub-wavelength structures. The relationship between the structure depth, width, aspect ratio and Z-axis defocus position of a single scan at different scanning speeds;

[0043] Among them, (a) is the relationship between the structural depth of a single scan and the Z-axis defocus position at the same scanning speed; (b) is the relationship between the structural width of a single scan and the Z-axis defocus position at the same scanning speed; (c) is the relationship between the depth-to-diameter ratio of a single scan and the Z-axis defocus position at the same scanning speed; where Z is the defocus amount, and the scale is 1μm;

[0044] Figure 5 The transmittance of the grating structure processed by single scribing when preparing sub-wavelength structures;

[0045] Among them, (a) is the transmittance of the single-stroke grating structure with different periods, and (b) is the transmittance of the variable-focus grating structure with different periods;

[0046] Figure 6 The relationship between the structure depth and the Z-axis defocus position when the laser Z-axis defocus position is changed when the first processing power is 234μw for preparing the sub-wavelength structure and the second scribing processing is performed with different laser powers at the same horizontal position;

[0047] Among them, (a) is the second scribing processing power of 234μw; (b) is the second scribing processing power of 468μw; (c) is the second scribing processing power of 690μw; (d) is the second scribing processing power of 836μw;

[0048] Figure 7 3D laser microscope measurement images measured on the sample surface at different defocus parameters when preparing sub-wavelength structures;

[0049] Among them, (a) is a 3D measurement laser microscope measurement image with the Z-axis defocus position inside the sample 5 μm above the surface; (b) is a 3D measurement laser microscope measurement image with the Z-axis defocus position inside the sample 3 μm below the surface;

[0050] Figure 8 To prepare the sub-wavelength structure, the transmittance of the grating structure and its physical image;

[0051] Among them, (a) is the transmittance of the grating structure with a variable focus processing period of 3μm, and (b) is the actual picture of the large-area sub-wavelength anti-reflection structure. DETAILED DESCRIPTION

[0052] In order to clearly and completely describe the technical solution and its specific working process of the present invention, the specific implementation methods of the present invention are as follows in conjunction with the accompanying drawings of the specification:

[0053] Example 1

[0054] The femtosecond laser wavelength used in this embodiment is 800nm, the pulse width is 190fs, the repetition rate is 1kHz, and the beam diameter is about 3mm. The first electrically controlled half-wave plate HWP1 and the second electrically controlled half-wave plate HWP2 are driven by a stepper motor. The focal length of the first convex lens L1 is 10cm, the focal length of the second convex lens L2 is 20cm, the focal length of the third convex lens L3 is 25cm, the focal length of the fourth convex lens L4 is 25cm, and the focal length of the fifth convex lens is 10cm. The focal length of the sixth convex lens is 10cm. The focal length of the seventh convex lens is 20cm. The first convex lens L1 and the second convex lens L2 form a beam expansion system, which expands the original femtosecond laser beam diameter by 2 times to 6mm, matching the entrance pupil diameter of the scanning galvanometer GS. The distance from the exit of the scanning galvanometer GS to the entrance pupil of the objective lens OL is 100cm. The third convex lens L3 is placed 20cm away from the exit of the scanning galvanometer GS, and the fourth convex lens L4 is placed 20cm away from the entrance pupil of the objective lens OL. Thus, the third convex lens L3 and the fourth convex lens L4 form a 4f system, and the diameter of the light beam reaching the entrance pupil of the objective lens OL is 6mm. The objective lens OL used is a Schwarzschild reflective objective lens with a working distance of 7.8mm, a numerical aperture NA=0.55, and a magnification of 50×. Its structure consists of a circular convex reflector and an annular concave reflector, wherein the circular convex reflector is fixed by three radiating blades. The three-dimensional displacement stage is assembled from four parts: a Z-axis piezoelectric positioning platform, a three-axis stepping motor, a two-axis adjustment platform, and a hollow sample stage. While ensuring that the LED light source below is transparent, the position of the sample can be electrically controlled and the Z-axis position of the sample can be precisely adjusted during the processing.

[0055] This embodiment provides a method for directly preparing an antireflection structure on the surface of an infrared window by combining a femtosecond laser three-dimensional galvanometer processing system with multi-channel focus multiplexing, which specifically includes the following steps:

[0056] (1) Sample fixation and dust removal system construction:

[0057] First, clamp the sample edge with a fixture specially made according to the shape, size and material of the sample, and then fix the fixture with screws and bolts to ensure that the fixture can firmly clamp the sample while avoiding damage to the sample. Use an air compressor to provide the gas source, and the gas route consists of a pipe with good sealing and high corrosion resistance, an adaptive needle-type blowing joint and a pressure regulating valve. Use a fixing rod to fix the blowing joint on the side of the translation stage so that it can directly act on the processing area, and then blow the gas directly to the processing area through the nozzle. Through the pressure regulating valve, control the parameters such as gas flow, pressure and blowing time.

[0058] (2) Leveling of the sample stage:

[0059] like Figure 1 As shown, the femtosecond laser emitted by the laser is expanded through the first convex lens L1 and the second convex lens L2, the light spot is enlarged by 2 times, and then passes through the first reflector R1, the scanning galvanometer GS, the third convex lens L3 and the fourth convex lens L4 in sequence. Then the laser passes through the second reflector R2 and enters the objective lens OL, and the optical axis of the first electrically controlled half-wave plate HWP1 at the laser exit is rotated so that the laser pulse energy after the second reflector R2 and before the entrance pupil of the objective lens OL is 10μj. Then the objective lens OL focuses the laser on the surface of the infrared window sample (diameter d = 12.7mm, thickness 2mm, produced by Yan Guo Jinghui). The illumination light emitted by the illumination light source LED above the hollow sample stage passes through the fifth L5, sixth L6 convex lenses, the third reflector R3, the second reflector R2, and then is reflected by the objective lens OL and the third convex lens L7 and focused on the high-definition camera CCD, so that the sample stage leveling process can be monitored in real time in the control computer. With the two perpendicular sides of the sample as the X-axis and Y-axis, the three-axis stepper motor is adjusted by computer to move between the two points (0, 0) and (1.5cm, 0), and the X-direction leveling knob is adjusted at the same time until the laser can scan a uniform damage line with a length of 1.5cm and a width of 5μm. At this time, the X-direction leveling is completed; similarly, the laser is used to draw a line between the two points (0, 0) and (0, 1.5cm) and the Y-direction leveling knob is used to level the Y direction; at this time, the laser can directly write a uniform width damage line in both the X and Y directions, indicating that the sample stage is perpendicular to the focused laser beam, the sample stage leveling is completed, and the position of the sample stage is fixed.

[0060] (3) Multi-channel focus multiplexing:

[0061] First, a reflective objective lens is selected as the objective lens OL and the CCD imaging system is used to focus the laser on the surface of the infrared window sample. Then, a scanning galvanometer and a high-precision three-dimensional displacement platform are combined to perform the first scribing process with a processing energy of 234μJ. Then, the laser spot focus position is changed, and the second scribing process is performed at the same horizontal position with appropriate laser power and scanning speed. Under the irradiation of the laser pulse, the initial grating structure is first generated at the original position. The power is maintained or changed by controlling the first half-wave plate HWP1, and the polarization direction is controlled by controlling the second half-wave plate HWP2. The scanning speed is controlled by the galvanometer combined with the three-dimensional displacement platform. Then, the laser focus is positively defocused (located above the surface) or negatively defocused (located below the surface) for the second or multiple scribing processes. The sub-wavelength structure of special size can be prepared by the multi-channel focus multiplexing method, which can reduce the refractive index gap between the air and the interface, effectively reduce the surface Fresnel reflection, and thus improve the transmittance.

[0062] In this embodiment, the laser power W1 used in the first processing is twice the surface damage threshold of the infrared window, the laser power W2 used in the second processing is 2-3 times the surface damage threshold of the infrared window, the scanning speed V1 used in the first processing is 10-20μm / s, and the scanning speed V2 used in the second processing is 20-30μm / s.

[0063] The scan results are as follows Figure 4 As shown: the processing depth basically changes with the Z-axis defocus position, and a depth peak will appear when the laser focus is positively defocused and negatively defocused, and the Z-axis defocus positions where the depth peaks appear at different scanning speeds are very similar. In most cases, as the scanning speed decreases, the depth of the formed structure increases accordingly. When the scanning speed is 500μm / s, the depth of the ablated structure does not change significantly, probably because the number of effective pulses on the infrared window surface decreases. When the scanning speed is reduced to 20μm / s, the processing structure depth is the deepest at 3μm negative defocus of the laser focus, the average depth is about 3.5μm, and the depth is relatively uniform. However, the power density decreases at positive defocus, which is not conducive to structure formation. However, the increase in power density caused by negative defocus can obtain a greater depth, which helps to obtain a larger aspect ratio.

[0064] like Figure 5 As shown in (a), when the grating structure period is 2.5μm, the transmittance increases significantly in the 4-14μm wavelength range, exceeds 80% in the 5.5-10.8μm wavelength range, and reaches a maximum of 85% at 6.5μm, which is about 10% higher than the transmittance of the untreated infrared window. When the grating structure period is 3μm, the transmittance exceeds 80% in the 6.5-10.5μm range, and the transmittance increases significantly in the 6-14μm range, and reaches a maximum of 85% at 7.7μm, which is about 9% higher than the transmittance of the untreated infrared window. When the grating structure period is 3.5μm, the transmittance increases significantly in the 7-14μm range, exceeds 80% in the 7.3-10.5μm range, and reaches a maximum of 83.5% at 8.5μm, which is 7.5% higher than the transmittance of the untreated infrared window. The transmittance of the prepared single-shot single-sided infrared window grating structure increases most significantly in the long-wave infrared band (8-14μm) when the structural period is 2.5-3.5μm. Figure 5As shown in (b), when the grating structure period is 2.5μm, the transmittance increases significantly in the range of 4-14μm, exceeds 80% in the range of 5.2-10.2μm, and reaches 86% at 6.2μm, which is about 11% higher than the transmittance of the untreated infrared window. When the grating structure period is 3μm, the transmittance exceeds 80% in the range of 6.5-12μm, and reaches 88% at the highest in the range of 8.2μm, which is about 12% higher than the transmittance of the untreated infrared window. When the grating structure period is 3.5μm, the transmittance increases significantly in the range of 7-14μm, exceeds 80% in the range of 7.7-12.2μm, and reaches 85% at the highest in the range of 10μm, which is 9% higher than the transmittance of the untreated infrared window.

[0065] The results show that when processing sub-wavelength structures on the surface of the infrared window, the method of multi-path focus multiplexing is used. That is, the grating structure that is processed twice with a moving focus has a significantly improved transmittance than the grating structure that is processed once, and the band coverage is wider. The grating structure with a period within 4μm has the best transmittance enhancement effect in the long-wave infrared range.

[0066] This embodiment proposes a method for preparing a transmittance-enhancing structure on the surface of an infrared window by using a femtosecond laser multi-path focus multiplexing method. By using a method of changing the focus position for secondary processing, an transmittance-enhancing grating structure on the surface of the infrared window is obtained. Figure 8 As shown, under the optimal parameters, the transmittance of the anti-reflection structure exceeds 80% in the range of 6.8-12.8μm, and exceeds 90% in the range of 7.3-12.1μm. The transmittance is the highest at 10μm, reaching 96%, which is about 20% higher than the transmittance of the untreated infrared window, showing very good transmission performance in the long-wave infrared band.

[0067] The preferred embodiments of the present invention are described in detail above in conjunction with the accompanying drawings. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.

[0068] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0069] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.

Claims

1. A method for preparing a high-performance antireflection structure on an infrared window surface based on femtosecond laser multi-focus multiplexing, characterized in that: The specific steps include: (1) Sample fixation and dust removal system construction; The specific steps are as follows: clamp the sample at the edge with a special fixture and fix the fixture with screws and bolts; use an air compressor to provide the gas source, and the gas route consists of a pipeline, an adapted needle-type air blowing joint and a pressure regulating valve; use a fixing rod to fix the needle-type air blowing joint on the side of the translation stage so that it can directly act on the processing area, and then blow the gas to the processing area through the nozzle of the needle-type air blowing joint; control the processing parameters through the pressure regulating valve to keep the gas state unchanged before leveling the sample stage and during the processing; (2) Leveling of the sample stage; (3) Multi-channel focus multiplexing combined with wet etching to prepare high aspect ratio and high transmittance sub-wavelength structures; The specific steps are as follows: during the first scanning process, the laser is first focused on the upper surface of the sample, the horizontal position remains unchanged, the laser power is set to W1, the scanning speed is set to V1, and a small-period subwavelength anti-reflection microstructure is prepared on the sample surface. Subsequently, the focus of the femtosecond laser is negatively defocused, the laser power is increased to W2, the scanning speed is increased to V2, and the polarization direction of the light beam is rotated 90° at the same time. The second processing is performed at the same horizontal position, and finally, combined with wet etching, a high-quality, high-aspect-ratio subwavelength structure is prepared on the surface of the infrared window.

2. The method for preparing a high-performance antireflection structure on an infrared window surface based on femtosecond laser multi-focus multiplexing as claimed in claim 1, characterized in that: In step (2), the leveling of the sample stage specifically includes the following steps: First, the femtosecond laser emitted by the laser passes through the first attenuation plate VDN1, and then is incident on the first convex lens L1 and the second convex lens L2 for beam expansion, and then is incident on the first half-wave HWP1, and then is incident on the first Glan prism GL1 after passing through the reflector R1, and then is uniformly incident on the entrance pupil of the scanning galvanometer GS after passing through the second half-wave plate HWP2, and then is emitted from the scanning galvanometer GS and passes through the third convex lens L3 and the fourth convex lens L4 respectively, and then is reflected by the reflector R2 and focused by the objective lens OL in turn, and then is incident on the infrared window sample surface on the hollow sample stage; the illumination light source LED is fixed above the hollow sample stage, so that the white light emitted by the illumination light source LED passes through the fifth L5 and the sixth convex lens L6 and then enters the objective lens OL; the illumination light passes through the reflector R2 and is reflected by the transmitting mirror R3 to the seventh convex lens L7 and is focused and imaged into the CCD, and finally the three-dimensional displacement stage and the CCD are connected to the computer terminal to monitor the leveling process of the sample stage in real time and level the sample stage.

3. The method for preparing a high-performance antireflection structure on an infrared window surface based on femtosecond laser multi-focus multiplexing as claimed in claim 2, characterized in that: The specific steps for leveling the sample stage are as follows: With the two perpendicular sides of the sample as the X-axis and Y-axis, the three-axis stepper motor is adjusted by computer to move between the two points (0, 0) and (1.5cm, 0), and the X-direction leveling knob is adjusted at the same time until the laser can scan a uniform damage line with a length of 1.5cm and a width of 5μm. At this time, the X-direction leveling is completed; similarly, the laser is used to draw a line between the two points (0, 0) and (0, 1.5cm) and the Y-direction leveling knob is used to level the Y direction; at this time, the laser can directly write a uniform width damage line in both the X and Y directions, indicating that the sample stage is perpendicular to the focused laser beam, the sample stage leveling is completed, and the position of the sample stage is fixed.

4. The method for preparing a high-performance antireflection structure on an infrared window surface based on femtosecond laser multi-focus multiplexing as claimed in claim 1, characterized in that: In step (3), the laser scanning method used is point-by-point scanning, and the spacing between each exposure point is in, is the focused spot diameter, λ is the laser wavelength, and NA is the numerical aperture of the objective lens OL.

5. The method for preparing a high-performance antireflection structure on an infrared window surface based on femtosecond laser multi-focus multiplexing as claimed in claim 1, characterized in that: In step (3), the laser power W1 used in the first processing is twice the surface damage threshold of the infrared window, the laser power W2 used in the second processing is 2-3 times the surface damage threshold of the infrared window, the scanning speed V1 used in the first processing is 10-20μm / s, and the scanning speed V2 used in the second processing is 20-30μm / s.

6. The method for preparing a high-performance antireflection structure on an infrared window surface based on femtosecond laser multi-focus multiplexing as claimed in claim 1, characterized in that: In step (3), the period of the small-period subwavelength anti-reflection microstructure prepared by the first processing is less than 4 μm.

7. The method for preparing a high-performance antireflection structure on an infrared window surface based on femtosecond laser multi-focus multiplexing as claimed in claim 1, characterized in that: In step (3), the polarization direction of the light beam is rotated 90°, specifically by controlling the second half-wave plate to change the polarization direction of the light beam into vertical polarization processing, and the scanning directions are two completely opposite directions perpendicular to the laser polarization.

8. The method for preparing a high-performance antireflection structure on an infrared window surface based on femtosecond laser multi-focus multiplexing as claimed in claim 1, characterized in that: In step (3), the wet etching is to heat the processed sample in a concentrated sulfuric acid solution water bath for a period of time, and then use a sodium hydroxide solution with a mass fraction of 5%-10% to corrode it.

Citation Information

Patent Citations

  • Laser processing method of semiconductor materials

    CN102896430A

  • Double-head laser machining device and machining method

    CN104972226A

  • Electronic dynamic regulation-based method for manufacturing surface-enhanced raman substrate

    CN107132210A

  • Near 4 pai spatial angle femtosecond laser direct writing processing method with depth continuous adjustable function and application

    CN109702323A

  • Method for processing phase tunable optical metasurface based on femtosecond laser

    CN111992890A

Cited By

  • Femtosecond laser processing method assisted by filling of refractive index matcher of porous material

    CN121199375A